Treatable inherited rare movement disorders. Issue 1 (1st September 2017) - Jinnah, H. A.; Albanese, Alberto; Bhatia, Kailash P.; Cardoso, Francisco; Da Prat, Gustavo; de Koning, Tom J.; Espay, Alberto J.; Fung, Victor; Garcia‐Ruiz, Pedro J.; Gershanik, Oscar; Jankovic, Joseph; Kaji, Ryuji; et al.
ABSTRACT: There are many rare movement disorders, and new ones are described every year. Because they are not well recognized, they often go undiagnosed for long periods of time. However, early diagnosis is becoming increasingly important. Rapid advances in our understanding of the biological mechanisms responsible for many rare disorders have enabled the development of specific treatments for some of them. Well‐known historical examples include Wilson disease and dopa‐responsive dystonia, for which specific and highly effective treatments have life‐altering effects. In recent years, similarly specific and effective treatments have been developed for more than 30 rare inherited movement disorders. These treatments include specific medications, dietary changes, avoidance or management of certain triggers, enzyme replacement therapy, and others. This list of treatable rare movement disorders is likely to grow during the next few years because a number of additional promising treatments are actively being developed or evaluated in clinical trials. © 2017 International Parkinson and Movement Disorder Society